Antifungal amphiphilic aminoglycoside K20: bioactivities and mechanism of action - Shrestha, Sanjib K.; Chang, Cheng-Wei T.; Meissner, Nicole; Oblad, John; Shrestha, Jaya P.; Sorensen, Kevin N.; Grilley, Michelle M.; Takemoto, Jon Y. (Frontiers in Microbiology, 2014)
K20 is a novel amphiphilic antifungal aminoglycoside that is synthetically derived from the antibiotic kanamycin A. Reported here are investigations of K20’s antimicrobial activities, cytotoxicity, and fungicidal mechanism of action. In vitro growth inhibitory activities against a variety of human and plant pathogenic yeasts, filamentous fungi, and bacteria were determined using microbroth dilution assays and time-kill curve analyses, and hemolytic and animal cell cytotoxic activities were determined. Effects on Cryptococcus neoformans H-99 infectivity were determined with a preventive murine lung infection model. The antifungal mechanism of action was studied using intact fungal cells, yeast lipid mutants, and small unilamellar lipid vesicles. K20 exhibited broad-spectrum in vitro antifungal activities but not antibacterial activities. Pulmonary, single dose-administration of K20 reduced C. neoformans lung infection rates 4-fold compared to controls. Hemolysis and half-maximal cytotoxicities of mammalian cells occurred at concentrations that were 10 to 32-fold higher than fungicidal MICs. With fluorescein isothiocyanate, 20 to 25 mg/L K20 caused staining of >95% of C. neoformans and Fusarium graminearum cells and at 31.3 mg/L caused rapid leakage (30 to 80% in 15 min) of calcein from preloaded small unilamellar lipid vesicles. K20 appears to be a broad-spectrum fungicide, capable of reducing the infectivity of C. neoformans, and exhibits low hemolytic activity and mammalian cell toxicity. It perturbs the plasma membrane by mechanisms that are lipid modulated. K20 is a novel amphiphilic aminoglycoside amenable to scalable production and a potential lead antifungal for therapeutic and crop protection applications.